2016
DOI: 10.1163/1568539x-00003320
|View full text |Cite
|
Sign up to set email alerts
|

Consistent long-term behavioural traits are linked to morphological defences in common carp (Cyprinus carpio)

Abstract: Individual prey often exhibit consistent behavioural differences in responses to risk. Here, we assess whether such behavioural consistency is linked to morphological changes that are known to result in differences in vulnerability to predators. Some fishes increase their depth-to-length ratio when under increased risk of predation, thereby reducing their risk to gape-limited predators. However, the development of these defences is limited by available resources. We asked whether behavioural tendencies associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Comparative studies of populations inhabiting environments that differ in natural predation pressure have shown that fish from high-predation environments have evolved larger caudal regions (muscular region anterior to the caudal fin from which substantial swimming power is generated) compared to their low-predation risk counterparts (Hendry et al, 2006;Langerhans, 2009a;Svanbäck et al, 2017). Moreover, a series of controlled experiments in different species of fish, manipulating individuals' perceived predation risk via exposure to predator presence/absence, have shown that predator presence induces deeper bodies (Abate et al, 2010;Brönmark & Miner, 1992;Chivers et al, 2007Chivers et al, , 2008Frommen et al, 2011;Vrtělová et al, 2016). Deeper bodies and larger caudal regions allow for enhanced fast-start performance (Domenici et al, 2008;Langerhans, 2009a), which in turn translates to an enhanced survival probability when confronted with predators (Langerhans, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of populations inhabiting environments that differ in natural predation pressure have shown that fish from high-predation environments have evolved larger caudal regions (muscular region anterior to the caudal fin from which substantial swimming power is generated) compared to their low-predation risk counterparts (Hendry et al, 2006;Langerhans, 2009a;Svanbäck et al, 2017). Moreover, a series of controlled experiments in different species of fish, manipulating individuals' perceived predation risk via exposure to predator presence/absence, have shown that predator presence induces deeper bodies (Abate et al, 2010;Brönmark & Miner, 1992;Chivers et al, 2007Chivers et al, , 2008Frommen et al, 2011;Vrtělová et al, 2016). Deeper bodies and larger caudal regions allow for enhanced fast-start performance (Domenici et al, 2008;Langerhans, 2009a), which in turn translates to an enhanced survival probability when confronted with predators (Langerhans, 2009a).…”
Section: Introductionmentioning
confidence: 99%